2007
DOI: 10.1111/j.1551-2916.2006.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Hot Isostatic Pressing of Cubic Boron Nitride–Tungsten Carbide/Cobalt (cBN–WC/Co) Composites: Effect of cBN Particle Size and Some Processing Parameters on their Microstructure and Properties

Abstract: Cubic boron nitride (cBN)-cemented carbide composites have gained attraction over the last few years because of their potential uses as wear parts. The densification behavior of cBN-hard metal composites by glass encapsulation hot isostatic pressinghas been investigated. Composites with different cBN grades (from 0/0.5 to 6/12 lm particle sizes) and cBN content (up to 50 vol%) were selected for this study. Near-full densification was obtained at temperatures between 11001 and 12001C, and pressures between 150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 12 publications
0
48
0
1
Order By: Relevance
“…Należy podkreślić, że im większa jest zawartość fazy twardej (cBN) w kompozycie, tym staje się on twardszy, bardziej wytrzymały mechanicznie oraz odporny na kruche pękanie, zmniejsza się natomiast jego odporność termiczna i chemiczna. Liczną grupę wśród wymienionych kompozytów stanowią materiały WCCo/cBN -uzyskane metodą izostatycznego prasowania na gorąco (HIP) [5], iskrowego spiekania plazmowego (SPS) [6,7] oraz impulsowego spiekania plazmowego (PPS) [8].…”
Section: Tablica I Skład Chemiczny I Właściwości żEliwa Sferoidalnegunclassified
“…Należy podkreślić, że im większa jest zawartość fazy twardej (cBN) w kompozycie, tym staje się on twardszy, bardziej wytrzymały mechanicznie oraz odporny na kruche pękanie, zmniejsza się natomiast jego odporność termiczna i chemiczna. Liczną grupę wśród wymienionych kompozytów stanowią materiały WCCo/cBN -uzyskane metodą izostatycznego prasowania na gorąco (HIP) [5], iskrowego spiekania plazmowego (SPS) [6,7] oraz impulsowego spiekania plazmowego (PPS) [8].…”
Section: Tablica I Skład Chemiczny I Właściwości żEliwa Sferoidalnegunclassified
“…4) were evenly surrounded by the binding cobalt phase, providing evidence that the high-current pulse sintering proceeded with participation of a liquid cobalt phase. When the sintering process occurs without participation of the liquid phase, cobalt usually occurs in the form of agglomerates and is distributed nonuniformly in the cemented carbide matrix [5], even though the sintering process is conducted at temperature of 1,100°C, which is below the melting point of cobalt.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the cBN particles can considerably increase the fracture toughness of the material due to the crack deflection effect, wherein crack energy is absorbed [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martínez and Echeberria 10) reported that the densification of WC-Co-cBN composites was significantly suppressed compared with that of WC-Co. Martín et al 24) also showed that the densification of cBN-Cu-Ti composites decreased by the addition of cBN. The relative density of monolithic BN prepared at 1500-1700°C for 600 s was 50-60%, resulting in almost the same density as BN compacts before sintering.…”
Section: Jcs-japanmentioning
confidence: 99%